PjBL Berbasis Scaffolding dalam Kreativitas Mahasiswa: Tinjauan dari Beban Kognitif dan Memori Kerja: Scaffolding-Based PjBL in Student Creativity: A Review of Cognitive Load and Working Memory - Rasydah Nur Tuada; Bilferi Hutapea; Fauziah A (ITScience (Information Technology and Science), 2025)
Creativity among prospective Physics teachers is very important. Still, the results of the final project are often not optimal due to the alleged high cognitive load, which limits working memory capacity. This study aims to analyse the effect of the scaffolding-based Project-based Learning (PjBL) model on Final Project Creativity, and to examine its role in moderating Cognitive Load and Working Memory. The study used a quantitative method with a quasi-experimental design (pretest-posttest non-equivalent control group design). The sample consisted of 34 students, divided into an experimental group (n=17) that implemented scaffolding-based PjBL and a control group (n=17) that implemented PjBL without scaffolding. Data analysis used MANCOVA. The MANCOVA results showed that scaffolding-based PjBL had a very significant effect on the combination of dependent variables (Wilks' Lambda, Sig.=0.000). Specifically, the experimental group showed lower Cognitive Load (Average=56.88) than the control group (Average=71.65). In addition, there was a significant increase in Creativity (Average 91.18 vs. 69.82) and Working Memory (Average 86.35 vs. 64.65). This finding was further validated by the Complex Span Task, which showed a 58% increase in working memory capacity in the experimental group. Scaffolding interventions have been proven effective in optimising cognitive processes by reducing extraneous cognitive load, thereby freeing up Working Memory capacity to facilitate deeper creative thinking processes. This study demonstrates the importance of structured support in managing cognitive load to enhance creativity.